The efficient synthesis of 3-R-6-thio-6,7-dihydro-2H-[l,2,4]triazino[2,3-c]-quinazoline-2-ones and their derivatives, antimicrobial and antifungal activity - Berest, G.G.; Voskoboynic, O.Yu.; Kovalenko, S.I.; Sinyak, R.S.; Ornelchenko, I.V.; Shishkin, O.V.; Kornarovska-Porokhnyavets, O.Z.; Novikov, V.P. (Журнал органічної та фармацевтичної хімії, 2010)
The reaction of 6-R-3-(2-aminophenyl)-1,2,4-triazin-5-ones (2) with carbon bisulphide leads to formation of potassium salts of 3-substituted 6-thio-6,7-dihydro-2H-[1,2,4]triazino[2,3-c]quinazoline-2-ones in the presence of potassium hydroxide or its “synthetic equivalent” potassium ethylxanthogenate in alcohols. Their alkylation with chloracetic acid snd its sunstituents occurs regioselectively. The structure of the compounds synthesized was confirmed by spectral data and X-ray diffraction analysis. The antimicrobial and antifungal activity of the compounds synthesized was tested against Escherichia coli, Aspergillus niger, Mycobacterium luteum, Candida albicans and Candida tenuis. Реакція 6-R-3-(2-амінофеніл)-1,2,4-триазин-5-онов (2) з сірковуглецем в етанолі у присутності калію гідроксиду або його “синтетичного еквіваленту” — калію етилксантогенату у спиртах призводить до утворення калієвих солей 3-заміщених 6-тіо-6,7-дигідро-2Н-[1,2,4]триазино[2,3-с]хіназолін-2-онів. Алкілування калієвих солей З-R-6-тіо-6,7-дигідро-2Н-[1,2,4]триазино[2,3-с]хіназолін-2-онів хлороцтовою кислотою та її заміщеними проходить 5-регіоселективно. Структура синтезованих сполук підтверджена спектральними і рентгєноструктурними методами аналізу. Антибактеріальна і антифунгіцидна активність синтезованих сполук вивчена на Escherichia coli, Aspergillus niger, Mycobacterium luteum, Candida albicans and Candida tenuis. Реакция 6-R-3-(2-аминофенил)-1,2,4-триазин-5-онов (2) с сероуглеродом в этаноле в присутствии калия гидроксида или его "синтетического эквивалента" — калия этилксантогената в спиртах приводит к образованию калиевых солей 3-замещенных 6-тио-6, 7-дигидро-2Н-[1,2,4]триазино[2,3-с]хиназолин-2-онов. Алкилирование калиевых солей 3-R-6-тио-6,7-дигидро-2Н-[1,2,4]триазино[2,3-с]хиназолин-2-онов хлоруксусной кислотой и ее замещенными проходит 5-региоселективно. Структура синтезированных соединений подтверждена спектральными и рентгеноструктурным методами анализа. Антибактериальная и антифунгицидная активность синтезированных соединений изучена на Escherichia coli, Aspergillus niger, Mycobacterium luteum, Candida albicans and Candida tenuis.